EFEKTIVITAS POWERPOINT INTERAKTIF TERHADAP LITERASI MATA PELAJARAN BAHASA INDONESIA KELAS 1 SDN PANGGUNG LOR SEMARANG - Dyah Ari Yani; Ikha Listyarini; Catur Prasetiawati; Henry Januar Saputra (LPPM Universitas Ekasakti, 2024)
This research aims to evaluate the effectiveness of using interactive PowerPoint in improving literacy in the Indonesian language subject for first-grade students at SDN Panggung Lor Semarang. In line with advances in information and communication technology, technology-based learning methods such as interactive PowerPoint are expected to improve the quality of education and student literacy from an early age. This research method uses a pretest and posttest method. Data were obtained through pretest and posttest on 28 students, with results showing a significant increase in the average score from 70.64 in the pretest to 92.46 in the posttest. The normality test using Shapiro-Wilk showed that the data were normally distributed. The homogeneity of variance test showed that the variance of the posttest data was homogeneous. These results indicate that the use of interactive PowerPoint not only improves students' learning outcomes but also reduces variation in their scores, indicating increased consistency in material comprehension. Thus, the use of interactive PowerPoint has proven effective in improving literacy and learning outcomes for first-grade students at SDN Panggung Lor Semarang.